2008
DOI: 10.1109/icassp.2008.4517600
|View full text |Cite
|
Sign up to set email alerts
|

Sound field decomposition using spherical microphone arrays

Abstract: Spherical microphone arrays offer a number of attractive properties such as direction-independent acoustic behavior and ability to reconstruct the sound eld in the vicinity of the array. Such ability is necessary in applications such as ambisonics and recreating auditory environment over headphones. We compare the performance of two scene reconstruction algorithms -one based on least-squares tting the observed potentials and another based on computing the far-eld signature function directly from the microphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…These cylindrical array results are consistent with similar simulations performed with spherical arrays in [10]. In particular, it is observed that the truncation number ps = p considered optimal in [9] is too high for use in real spherical and cylindrical beamforming applications as numerical problems arise even in a simulated setup.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…These cylindrical array results are consistent with similar simulations performed with spherical arrays in [10]. In particular, it is observed that the truncation number ps = p considered optimal in [9] is too high for use in real spherical and cylindrical beamforming applications as numerical problems arise even in a simulated setup.…”
Section: Resultssupporting
confidence: 86%
“…The regularization parameter is related to the condition number of F . It was shown in [10] that the specific value of within reasonable bounds (from 10 7 to 10 2 relative to the elements of ) only marginally in uences the decomposition results.…”
Section: Least-squares (Ls) Decompositionmentioning
confidence: 97%
See 3 more Smart Citations